Amdi Giraybay'ın şiirleri, metin, dil incelemesi, sözlük - Deniz, Pelin (İstanbul Kültür Üniversitesi / Sosyal Bilimler Enstitüsü / Türk Dili ve Edebiyatı Anabilim Dalı / Türk Dili ve Edebiyatı Bilim Dalı, 2014)
Bu çalışmada Kırım Tatar şairi Hamdi Giraybay'ın şiirlerinin toplandığı şiir kitabı incelendi. Tez çalışmasında önce elimizdeki Kiril alfabeli şiirler Latin alfabesine aktarıldı. Daha sonra şiirler Türkiye Türkçesine aktarıldı. Aktarılan şiirler dil yapısı açısından incelendi ve bir sözlük hazırlandı. Bu işlemler sırasıyla tamamlandıktan sonra şiirler yüzeysel olarak konularına göre ayrıldı. Bu çalışmada şiirler şekil bilgisi açısından değerlendirilmiştir. Ayrıca Kırım Tatar Türkçesindeki sözcüklerle Türkiye Türkçesindeki sözcükler arasında benzerlik ve farklılıklar bir kez daha görülmüştür. Tez çalışması kaynak kitabının temini ve seçimi konusunda yardım ve desteklerini hiçbir zaman esirgemeyen, çalışmamın her aşamasını takip eden ve bana yeni ufuklar açan, sayın danışmanım Prof. Dr. Vahit Türk'e sonsuz teşekkürlerimi sunarım. Şiirleri Türkiye Türkçesine aktarırken bana yardım eden arkadaşım Dr. Reşide Hacıömerova'ya çok teşekkür ederim. Ayrıca her zaman yanımda olan ve hiçbir yardımını esirgemeyen canımdan çok sevdiğim biricik aileme sonsuz teşekkür ederim

In this thesis, the book which contains poems by the Crimean Tatar poet Hamdi Giraybay was studied. To start with, the available Kiril alphabet poems were translated into the Latin alphabet. Subsequently, these poems were translated into Turkish spoken in Turkey after long detailed studies. Translated poems were examined by taking into consideration the use of words in the construction of phrases and sentences - "syntax" and the study of the internal structure of words -"morphology". Once these steps were completed respectively, the poems were sorted superficially by their subjects. In this study the poems are evaluated by their internal structure of words "morphology". Furthermore, the differences and the similarities between Crimean Turkish and Turkish spoken in Turkey are discussed once again. I would like to take this opportunity to thank my mentor and adviser Prof. Dr. Vahit Türk, who had helped me choosing and providing the book which was taken as a source for the thesis for his continuous support (and for following up the every step of the thesis with me). Also I would like to thank my dear friend Dr. Reşide Haciömerova for her help during the translation of the poems into Turkish. Last but not least, I thank my dear parents for being by my side at all times and for their continuous support.
Keywords: Biçimbilim; Morphology; Dilbilim; Linguistics; Kırım Tatarcası; Crimean Tatar language; Kırım Tatarları; Crimean Tatars; Kırım edebiyatı; Crimean literature